Age as a historical materialist concept in cultural-historical theory of human development - Chaiklin, Seth (Obutchénie. Revista de Didática e Psicologia Pedagógica, 2019)
The concept of age has a central role in the theoretical structure of L. S. Vygotsky’s approach to analysing child development. This concept is presented in the first part of this article. The presentation is organized around three conceptual challenges, the role or function of the age concept in a theory of human development, the psychological “content” of an age, and how to evaluate development in relation to an age. Main points include: (a) age, as a psychological concept, is formed through historical, material practice, (b) the concept has practical importance, but (c) for the most part the concept is still only a theoretical sketch. The second part of the article takes up methodological problems involved in working with and further developing this theoretical concept. Use of the concept in relation to pedagogical interventions may be especially productive.